The Unified Approach of Ionizing Radiation on Biological Matter: Action of Heavy Charged Particles on Mammalian Cells - Alkharam , Ali S. (Scientific Journal for Faculty of Science-Sirte University, 2022)
Damaging effects to mammalian cells by heavy charged particles have been realized in terms of the mean free path for linear primary ionization (the spacing of ionizing events along the charged particle tracks) using in vitro radiobiological experimentation data. Damage is found to be optimum when the mean free path for linear primary ionization along the tracks in the cell nucleus matches the mean chord length of approximately 1.8 nm through a DNA segment. A simple semi-theoretical model is proposed to define absolute biological effectiveness based on effect inactivation cross section s (mm2) which is interrelated to the mean free path for linear primary ionization l. For heavy charged particles, the model shows a saturation region for the effect cross section, ss = 60 mm2 for l ≤ 1.8 nm. The model explains the mechanisms leading to cell death via DNA strand scissions. In the saturation region, double strand breaks of the DNA are predominant, unrepaired or mismatched repair processes lead to maximum damage. At higher mean free path; l > 1.8 nm, single strand breaks of the DNA is the main basic mechanism and thus repairable processes are possible.